Community-based Study on Self-medication Practices and their Determinants at Kahun Danda, Pokhara - Manandhar, Varsha; Upadhyaya, Baidehi; Bhusal, Krishna; Duwadi, Kapil; Adhikari, Ranju; Wagle, Pratisma; Sapkota, Ujjwal (Nepal Journal of Medical Sciences, 2024)
Introduction: Taking any allopathic or alternative medicine without the doctors' prescriptions, re-using old prescriptions to acquire medicine, sharing medicines with friends or family and taking leftover medications to alleviate symptoms is termed self-medication. There can be chances of inappropriate use, serious adverse effects and delay in seeking medical care as a result. This study was conducted to assess the prevalence of self-medication practices in Kahun Danda of Pokhara, Nepal. Methods: A cross-sectional study was conducted among 105 residents of Kahun Danda, using a semi-structured questionnaire. One participant from each household selected for family health study was chosen as respondent (Convenience sampling). Data collection was started after getting ethical approval from Institutional Review Committee of Manipal College of Medical Sciences (Reference number MCOMS/IRC/541/GA). The collected data was entered in Ms Excel 2010 and exported to SPSS version 21.0 for data analysis. Frequencies with proportions were calculated for categorical variables, while mean with standard deviation were calculated for continuous variables. A chi-square test was applied to find the association between self-medication practices and different independent variables, taking p-value less than 0.05 as statistically significant at 95% confidence interval. Results: Self-medication practice was found in 79 (75.24%) participants, with cough and cold, headache and fever being the most common indications. Age of the participants was found to have statistically significant association with self-medication practice (p-value 0.02), with all participants above 40 years of age found to have practiced self-medication. Perception of suffering from minor ailments (54, 68.40%) was the main reason behind choosing self-medication over a visit to a health facility. Conclusions: Self-medication practice was found to be very high among the residents of Kahun Danda, with antipyretics being the most used medication. All participants above 40 years of age were involved in self-medication practices and most of them perceived their ailments to be of minor nature.